Nutritional Challenges in Pregnant Women with Renal Diseases: Relevance to Fetal Outcomes - Esposito, Pasquale (Nutrients, 2020)
Pregnancy in women affected by chronic kidney disease (CKD) has become more common in recent years, probably as a consequence of increased CKD prevalence and improvements in the care provided to these patients. Management of this condition requires careful attention since many clinical aspects have to be taken into consideration, including the reciprocal influence of the renal disease and pregnancy, the need for adjustment of the medical treatments and the high risk of maternal and obstetric complications. Nutrition assessment and management is a crucial step in this process, since nutritional status may affect both maternal and fetal health, with potential effects also on the future development of adult diseases in the offspring. Nevertheless, few data are available on the nutritional management of pregnant women with CKD and the main clinical indications are based on small case series or are extrapolated from the general recommendations for non-pregnant CKD patients. In this review, we discuss the main issues regarding the nutritional management of pregnant women with renal diseases, including CKD patients on conservative treatment, patients on dialysis and kidney transplant patients, focusing on their relevance on fetal outcomes and considering the peculiarities of this population and the approaches that could be implemented into clinical practice.